2015
DOI: 10.1002/14651858.cd003357.pub4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilisation for unexplained subfertility

Abstract: BackgroundOne-third of subfertile couples have no identifiable cause for their inability to conceive. In vitro fertilisation (IVF) is a widely accepted treatment for this condition; however, this treatment is invasive and expensive and is associated with risks. ObjectivesTo evaluate the e ectiveness and safety of IVF compared with expectant management, unstimulated intrauterine insemination (IUI) or intrauterine insemination along with ovarian stimulation with gonadotropins (IUI + gonadotropins) or clomiphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 29 publications
0
53
2
1
Order By: Relevance
“…The results also demonstrated that the cost per live birth for IVF was less than that for IUI. Our results differ from those of older comparisons of IUI and IVF, but there is heterogeneity between these studies . More recent studies have also produced variable results.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The results also demonstrated that the cost per live birth for IVF was less than that for IUI. Our results differ from those of older comparisons of IUI and IVF, but there is heterogeneity between these studies . More recent studies have also produced variable results.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore Pandian et al . found a higher multiple pregnancy rate in women who underwent SO/IUI compared with IVF, but this did not reach statistical significance …”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Cycle length was set at 1 month. We used a time frame of 3 years because the chances of natural conception in couples with unexplained subfertility within these 3 years are substantial . The outcome was defined as a live birth of at least one child.…”
Section: Methodsmentioning
confidence: 99%